1999
DOI: 10.1039/a903034d
|View full text |Cite
|
Sign up to set email alerts
|

Determination of selected microbial volatile organic compounds by diffusive sampling and dual-column capillary GC-FID-a new feasible approach for the detection of an exposure to indoor mould fungi?

Abstract: A new, analytically valid procedure is described to assess the exposure of human beings to the so-called microbial volatile organic compounds (MVOCs) in air. The method can be used routinely for large sample numbers and is especially valuable as a basis for further research on the correlation between single MVOCs and indoor mould growth. The procedure is based on the fact that fungi produce a variety of volatile organic compounds, such as 3-methylbutan-1-ol, 3-methylbutan-2-ol, fenchone, heptan-2-one, hexan-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 20 publications
(3 reference statements)
3
46
1
Order By: Relevance
“…The recommended maximum level of 1-octen-3-ol for indoor air, based on data from animal studies, is estimated to be 100 µg/m 3 (Korpi et al, 1999). Actual average indoor MVOC concentrations in dwellings have been found to be up to 2 µg/m 3 (Araki et al, 2009;Elke et al, 1999;Matysik et al, 2009), which is far lower than those found in experimental studies and than the recommended maximum level. In response to these findings, one study suggested that the apparent relationship between health outcomes and MVOCs could be due to exposure to the microorganisms themselves (Smedje et al, 1996).…”
Section: Microbial Volatile Organic Compounds (Mvocs) Include a Rangementioning
confidence: 80%
See 1 more Smart Citation
“…The recommended maximum level of 1-octen-3-ol for indoor air, based on data from animal studies, is estimated to be 100 µg/m 3 (Korpi et al, 1999). Actual average indoor MVOC concentrations in dwellings have been found to be up to 2 µg/m 3 (Araki et al, 2009;Elke et al, 1999;Matysik et al, 2009), which is far lower than those found in experimental studies and than the recommended maximum level. In response to these findings, one study suggested that the apparent relationship between health outcomes and MVOCs could be due to exposure to the microorganisms themselves (Smedje et al, 1996).…”
Section: Microbial Volatile Organic Compounds (Mvocs) Include a Rangementioning
confidence: 80%
“…Two studies on MVOC exposure and asthma and allergies in schools found a relationship between MVOC exposure and an increased odds ratio (OR) for the occurrence of wheezing, nocturnal breathlessness, doctor-diagnosed asthma, and history of asthma among pupils and among employees (Kim et al, 2007;Smedje et al, 1996). There has been only one study of the home setting, which found that children living in dwellings with higher MVOC concentrations had a higher prevalence of asthma, hay fever, and wheezing, and the results were not statistically significant (Elke et al, 1999).…”
Section: Microbial Volatile Organic Compounds (Mvocs) Include a Rangementioning
confidence: 99%
“…Similar to our results, Wady et al (2003) detected 2-pentanol, 3-octanone, 1-octen-3-ol and 2-methyl-1-butanol for cultures of A. penicillioides isolated from mineral wood onto DG18 medium. For E. chevalieri, the only similar compound compared to Elke et al (1999) was 3-methylbutan-1-ol regarding the analysis of Eurotium species isolated from indoor dust samples on DG18 medium.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1990s, MVOCs are often discussed to be associated with the sick building syndrome (SBS) because of their suspected role as responsible for a wide range of specific and non-specific symptoms and discomfort (Elke et al, 1999;Larsen et al, 1998;Matysik et al, 2008;Meyer et al, 1998;Wessén and Schoeps, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…From several so-called MVOCs analysed by Elke et al [30] in damp and mouldy houses, 3-methylbutan-1-ol, hexan-2-one, heptan-2-one and octan-3-ol were found to be the most reliable indicators for mould formation. A correlation was found between Aspergillus sp, and heptan-2-one, hexan-2-one, octan-3-ol, octan-3-one and alpha-terpineol, while the occurrence of Eurotium sp.…”
Section: Microbial Volatile Organic Compoundsmentioning
confidence: 99%